Impact of Job Satisfaction and Organizational Culture on Service Quality in Central Maluku Regency - Edward Teubun; Hendry Selanno; Elake Nataniel (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the Study: This study aims to examine the influence of job satisfaction and organizational culture on improving service quality at the Investment and One-Stop Integrated Service Office of Central Maluku Regency. The focus is to determine which internal factors significantly drive better public service quality. Methodology: The study applies a quantitative approach using a survey method. Data were collected with structured questionnaires from 38 employees for the independent variables and 100 service users for service quality. Multiple regression analysis and hypothesis testing were performed using SPSS software to evaluate variable relationships. Main Findings: The results show that all independent variables collectively have a significant effect on service quality. However, partial testing indicates that only job satisfaction has a positive and significant impact on service quality. Employee performance shows a negative and non-significant effect, while organizational culture does not significantly influence service quality improvement at the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu the Investment and One-Stop Integrated Service Office of Central Maluku Regency. Novelty/Originality of this Study: This study highlights the contrasting effects of internal organizational factors on public service quality by showing that job satisfaction is the only significant driver. The finding provides new insight into prioritizing human resource policies in public service institutions where organizational culture and employee performance may not directly enhance service outcomes.